Changing Prospects for Trade Unionism: Comparisons between Six Countries - Wheeler, Hoyt N. (Relations industrielles / Industrial Relations, 2003)
Changing Prospects for Trade Unionism: Comparisons between Six Countries, edited by Peter Fairbrother and Gerard Griffin, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Comparative analysis; Labor Unions; Labor relations; Manycountries; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unionization